FOLR1-Targeted Oxygen-Delivering Nanosomes Enhance Chemo-Induced Apoptosis in Hypoxic Cancer - Lee G; Kim J; Yang J; Jang Y; Jang J; Tanaka M; Niepa THR; Lee HY; Choi J (International Journal of Nanomedicine, 2025)
Gahyun Lee,1 Jiwon Kim,1 Jihyuk Yang,1 Yerin Jang,1 Jaehee Jang,1 Masayoshi Tanaka,2 Tagbo HR Niepa,3,4 Hee-Young Lee,5 Jonghoon Choi1,6,7 1School of Integrative Engineering, Chung-Ang University, Seoul, 06974, Republic of Korea; 2Department of Chemical Science and Engineering, Tokyo Institute of Technology, Yokohama-shi, Kanagawa, 226-8503, Japan; 3Department of Chemical Engineering, Carnegie Mellon University, Pittsburgh, PA, 15213, USA; 4Department of Biomedical Engineering, Carnegie Mellon University, Pittsburgh, PA, 15213, USA; 5Department of Chemical Engineering, Kumoh National Institute of Technology, Gumi, 39177, Republic of Korea; 6Feynman Institute of Technology, Nanomedicine Corporation, Seoul, 06974, Republic of Korea; 7Feynman Institute of Nanomedicine, Nanopeutics Inc, Lewes, DE, 19958, USACorrespondence: Jonghoon Choi, Email nanomed@cau.ac.kr Hee-Young Lee, Email lhysshr@kumoh.ac.krBackground: The rapid proliferation of tumor cells increases oxygen demand, while the underdeveloped vasculature limits supply, leading to hypoxia in the tumor microenvironment. This hypoxic condition is a hallmark of solid tumors and contributes to tumor progression, immune suppression, metastasis, and resistance to therapy.Purpose: This study aimed to counteract tumor hypoxia and improve therapeutic outcomes by delivering both oxygen and the chemotherapeutic agent doxorubicin directly to tumors.Methods: HON_FA@DOX, a folate-functionalized and perfluorohexane-enhanced liposomal nanosome co-loaded with oxygen and doxorubicin, was developed and characterized based on its physical properties. Its tumor-targeting capability, oxygen delivery efficiency, and therapeutic potential were evaluated under in vitro conditions. Cellular experiments were conducted to assess selective binding, hypoxia modulation, cytotoxicity, and the expression of genes related to apoptosis.Results: HON_FA@DOX exhibited a doxorubicin encapsulation efficiency of 36.6% and an enhanced oxygen loading capacity of 23.2 mg/L. The nanosomes demonstrated selective binding to FOLR1-expressing tumor cells and sustained release of doxorubicin. This dual-delivery system effectively alleviated hypoxia within the tumor microenvironment and reduced the expression of the hypoxia-related gene HIF-1α by 50%. Furthermore, HON_FA@DOX treatment significantly increased the expression of apoptosis-related genes and mitigated chemotherapy resistance, thereby enhancing the overall anticancer efficacy.Conclusion: We demonstrated that multifunctional nanosomes delivering both oxygen and doxorubicin effectively alleviated tumor hypoxia and reduced chemotherapy resistance, thereby enhancing anticancer efficacy. This approach presents a promising strategy for addressing tumor hypoxia and may be broadly applicable as an adjunct to conventional cancer therapies.Keywords: liposome, oxygen delivery, drug delivery, hypoxia, HIF, chemoresistance, folate, FOLR1, doxorubicin, chemotherapy